2000
DOI: 10.1128/aac.44.8.2205-2206.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity and Fecal Concentration of Rifaximin after Oral Administration

Abstract: Rifaximin showed moderately high MICs (the MIC at which 90% of the isolates tested were inhibited ‫؍‬ 50 g/ml) for 145 bacterial enteropathogens from patients with traveler's diarrhea acquired in Mexico during the summers of 1997 and 1998. Rifaximin concentrations in stool the day after oral administration (800 mg daily for 3 days) were high (average, 7,961 g/g), proving the value of the drug.Bacterial agents are known to be the major cause of traveler's diarrhea. It has been shown that antibacterial agents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 11 publications
2
123
1
8
Order By: Relevance
“…Рифаксимін не адсорбується кишечником [11,42,88,109], тому його виявляють у фекаліях у високих концентраціях [46]. Діє на грампозитив-ні та грамнегативні бактерії товстої кишки [88,109].…”
Section: загальна характеристика препаратівunclassified
See 1 more Smart Citation
“…Рифаксимін не адсорбується кишечником [11,42,88,109], тому його виявляють у фекаліях у високих концентраціях [46]. Діє на грампозитив-ні та грамнегативні бактерії товстої кишки [88,109].…”
Section: загальна характеристика препаратівunclassified
“…Діє на грампозитив-ні та грамнегативні бактерії товстої кишки [88,109]. Цей антибіотик активний щодо бактерій E. coli, представників родів Salmonella і Shigella, тому, як і ципрофлокса-цин, його застосовують для лікування діареї [46,103].…”
Section: загальна характеристика препаратівunclassified
“…In addition, a pharmacokinetic study reported an extremely high fecal concentration of rifaximin after oral ingestion [Jiang et al 2000]. Nevertheless, the in vivo effect of rifaximin was disappointing in patients in whom invasive pathogen(s) were isolated [Taylor et al 2006].…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%
“…When radiolabeled rifaximin was administered orally, the bioavailability of rifaximin was less than 0.4% in the blood and urine, and 97% was recovered unchanged in stool [Descombe et al 1994]. After the oral administration of 400 mg rifaximin twice a day for three days to travelers with diarrhea, its fecal level reached extremely high concentrations up to the range of 40008000 mg/g [Jiang et al 2000].…”
Section: Rifaximin Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation